Sexual orientation and household decision making: Same-sex couples' balance of power and labor supply choices - Sonia Oreffice (Fondazione Eni Enrico Mattei (FEEM), 2008)
I estimate how intra-household bargaining affects gay and lesbian couples' labor supplies, investigating their similarity to heterosexual decision-making, in a collective household framework. Data from the 2000 US Census show that couples of all types exhibit a significant response to bargaining power shifts, as measured by differences between partners in age or non-labor income. In gay, lesbian, and heterosexual cohabiting couples, a relatively young or rich partner has more bargaining power and hence supplies less labor, the opposite holding for his/her mate. Married couples value the older spouse instead, or the richer. No effects are found for same-sex roommates.
Keywords: D1; J22; 330; Household Decision Making; Same-Sex Couples; Labor Supply